Long‐term survival in elderly patients with stable coronary disease. (9th May 2013) - Ruiz Ortiz, Martín; Ogayar, Cristina; Romo, Elías; Mesa, Dolores; Delgado, Mónica; Anguita, Manuel; Castillo, Juan C.; Arizón, José M.; Suárez de Lezo, José
Abstract Background This study aimed to assess long‐term prognosis of stable coronary artery disease (sCAD) in patients aged ≥ 75 years and to identify clinical predictors of cardiovascular and overall mortality. Materials and Methods From February 2000 to January 2007, 391 outpatients aged ≥ 75 years (median 78 years, interquartile range [IQR] 76–81 years, 66% male) with sCAD were recruited in this prospective cohort study. Associations of baseline variables with long‐term cardiovascular and all‐cause death were investigated. Results After up to 11 years of follow‐up (median 4 years, IQR 2–6 years), 89 patients died (23%, 5·45%/year), 35 from cardiovascular causes (9%, 2·14%/year). Multivariate analysis identified family history of coronary disease (HR 4·28, 95% CI 1·22–15·02, P = 0·02), baseline atrial fibrillation (HR 3·18, 95% CI 1·37–7·39, P = 0·007), age (HR 1·61 per 5 year increase, 95% CI 1·04–2·50, P = 0·03), resting heart rate (HR 1·26 per 5 bpm increase, 95% CI 1·09–1·47, P = 0·003) and previous revascularization (HR 0·17, 95% CI 0·04–0·77, P = 0·02) as independent predictors of cardiovascular death, and previous acute coronary syndrome (HR 4·93, 95% CI 1·49–16·30, P = 0·009), baseline atrial fibrillation (HR 1·96, 95% CI 1·12–3·43, P = 0·02), tobacco use (HR 1·69, 95% CI 1·00–2·84, P = 0·049 for ex‐smoking and HR 6·78, 95% CI 0·89–51·47, P = 0·06 for active smoking), age (HR 1·58 per 5 year increase, 95% CI 1·18–2·11, P = 0·002), resting heart rate (HR 1·10 per 5 bpm increase, 95% CI 1·00–1·22, P = 0·05) and diastolic blood pressure (HR 0·97, 95% CI 0·94–0·99, P = 0·01) as independent predictors of overall mortality. Conclusions In this study, 4‐years overall mortality was 23% among elderly patients with sCAD. Simple clinical variables can identify patients at higher risk of mortality.